2015
DOI: 10.1186/s40792-015-0102-9
|View full text |Cite
|
Sign up to set email alerts
|

Successfully treated advanced esophageal cancer with left axillary lymph node metastasis and synchronous right breast cancer: a case report

Abstract: The incidence of double cancer of the esophagus and breast is rare, and axillary lymph node metastasis (ALM) in esophageal cancer is also very rare. We report a case of advanced esophageal cancer with left ALM and synchronous right breast cancer. A 64-year-old woman was admitted to our hospital with dysphagia. The clinical diagnosis was esophageal cancer (T3N0M1 stage IV) and right breast cancer (T1cN0M0 stage I). She was initially treated with triple chemotherapy with docetaxel, cisplatin, and 5-fluorouracil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A similar finding was reported in patients with lung cancers[ 4 5 ] and also in a case report of a patient with synchronous double cancers of the esophagus with left ALNM and a right breast primary, prompting the author's to suggest a second theory of a possible direct lymphatic spread to the axillary lymph nodes bypassing the supraclavicular lymph nodes. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported in patients with lung cancers[ 4 5 ] and also in a case report of a patient with synchronous double cancers of the esophagus with left ALNM and a right breast primary, prompting the author's to suggest a second theory of a possible direct lymphatic spread to the axillary lymph nodes bypassing the supraclavicular lymph nodes. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…A clear delineation is described with improved quality of life measures despite the terminality of the primary cancer. Concurrently, 14 studies noted statistically significant survival rates in individuals who underwent palliative mastectomy [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Of these aggregates, three studies noted no difference in patient survival outcome and concluded with conflicting data [25][26][27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, most cases of double primary cancer are metachronous, and there are few cases in which both cancers were treated simultaneously. Surgery was chosen for all of these cases [4,5], and there were no cases in which treatment other than surgery was chosen because of multiple metastases or advanced cancer.…”
Section: Introductionmentioning
confidence: 99%